Pengaruh Perputaran Kas, dan Perputaran Piutang terhadap Profitabilitas pada Perusahaan manufaktur - Nur Zarliani Uli; Endi Rustendi; Dany Luqyana Idris; Eva Yuniarti Utami; Wiwit Agustina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect of cash turnover and expense turnover on profitability in manufacturing companies. Secondary data used in this study are financial reports of manufacturing companies listed on the IDX for the period 2020-2023. The independent variables in this study are cash turnover and billing turnover, while the dependent variable is profitability. The analysis method used in this study is panel data regression analysis, determination coefficient test (R2), F test and t test. The results of this study are cash turnover and billing turnover simultaneously have a significant effect on profitability. However, in a partial analysis, it shows that cash turnover partially has a significant effect on profitability. While financial turnover partially does not have a significant effect on profitability.